NMR metabolic fingerprinting and chemometrics driven authentication of Greek grape marc spirits. (1st April 2016) - Fotakis, Charalambos; Zervou, Maria
Highlights: NMR foodomics authenticate the Macedonian tsipouro and the Cretan tsikoudia. Novel NMR foodomics study of Xinomavro, Malvasia, Romeiko, Sangiovese, Nebbiolo . Metabolic trends framed in grape marc spirits are presented in color coded tables. The impact of the blending procedure on grape marc distillates is investigated. Validation steps protect models against over-fitting and ensure unbiased results. Abstract: NMR metabolomics was used to investigate 57 Greek spirits of four indigenous and four international varieties from Macedonia (tsipouro) and Crete (tsikoudia) to establish their authenticity. The metabolic profile of Romeiko, Malvasia, Xinomavro, Sangiovese and Nebbiolo varieties was assessed for the first time. The WET1D sequence was used to improve sensitivity and unveil minor metabolites. PCA was applied to delineate the provenance of samples and associate metabolites with distinct varietal characteristics, such as the acidity of Sangiovese, the overripe grapes harvesting of Romeiko, the intense body of Cabernet Sauvignon, the light body of Xinomavro and the glutamic acid for Malvasia . The migration of Cabernet Sauvignon from north Greece to Crete was framed. Monitoring multi-varietal spirits introduced 2-vinylethanol as a marker for yeast selection. OPLS-DA was applied to samples from the same vineyard, thus highlighting genotypic markers. Consequently, the findings address the concepts of typicity and traceability in grape marc spirits.